Judicial decisions in international law argumentation : between entrapment and creativity - Lo Giacco, Letizia, 1985- (London [England] : Hart Publishing, 2022)
"How do the decisions of courts, when adjudicating statutory rules, contribute to the transformation of international law? This monograph explores this question, looking specifically at questions of international criminal law. It shows how courts take both a creative and constraining approach, allowing themselves to be guided by precedent but departing from it by argumentation if required. This is not an insignificant finding: it essentially allows for the rules of international criminal law to be rewritten but, more fundamentally, their ideological underpinning to be revisited. The author tracks how courts have decided cases in four key fields: protected groups in the definition of genocide; armed conflict in the definition of war crimes and serious violations of the laws and customs of war; command responsibility; the question of the 'unlawful combatant. Cases are drawn from courts including the International Military Tribunal in Nuremberg (IMT), the ICTY, the ICTR, and the ICC. This innovative work offers a new way of considering the role of the courts in transforming international law."--
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: International criminal courts -- Rules and practice; International criminal courts -- Case studies; Criminal procedure (International law); Electronic books